Legal Policies Against Crimes of Trafficking in Persons - Prakoso, Abdul Rahman; Nurmalinda, Putri Ayu (Law Research Review Quarterly, 2018)
Trafficking in persons which is currently still a problem in people's lives. Trafficking in persons includes the recruitment process to the buying and selling of people. The existence of Law Number 21 Year 2007 concerning Eradication of Criminal Acts of Trafficking in Persons as protection for acts of trafficking in persons. Legal policy in the realm of trafficking does not only involve elements of the central government but also relates to policies issued by local governments. The law as a regulatory instrument in Indonesia is based on the existence of regional policies to protect its citizens. Trafficking in persons is inseparable from various parties. This concerns various aspects of the community elements involved in it. Comprehensive prevention is needed to prevent trafficking in persons. In this case the position holder as well as law enforcement must play a role in the enforcement and protection of trafficking in persons.